ATTITUDES OF CZECH DENTAL CHAMBER MEMBERS TO THE COVID-19 PANDEMIC MEASURES IMPLEMENTED IN DENTAL PRACTICES - V Peřina; R Šmucler; J Treglerová; N Pilbauerová; M Kunderová; J Schmidt (Czech Dental Chamber, 2022)
Introduction, aim: This work describes the attitudes of Czech Dental Chamber members to anti-epidemic measures during the COVID-19 pandemic. Responses are further classified according to the respondents' COVID-19 status.Method: The data were obtained via an online questionnaire survey from June 23 to September 4, 2021.Results: A total of 2716 members of the Czech Dental Chamber participated in this survey, representing 24.3% of all chamber members. Almost 90% of the respondents considered the official recommendation against the transmission of SARS-CoV-2 infection issued by the Czech Dental Chamber to be adequate, approximately 6% insufficient, and 4% too strict. The prevalence of COVID-19 in the group considering the recommendation too strict was statistically significantly higher compared to the group considering the recommendation to be adequate(p = 0.0345, odds ratio (OR) 1.592). The respondents who performed COVID-19 testing in their practices showed a statistically significantly higher percentage of detected COVID-19 infections (p < 0.0001, OR 1.883). Almost three-quarters of respondents want to maintain strict anti-epidemic measures even after the pandemic; this commitment is statistically significantly higher for the respondents who did not have COVID-19 (p = 0.0041, OR 1.511). COVID-19 infection did not affect the willingness to be vaccinated against influenza. In contrast, the respondents with a positive attitude towards vaccination against COVID-19 showed a statistically significantly higher willingness to get vaccinated against the flu (p < 0.0001, OR 10.36).Conslusion: The prevalence of COVID-19 was statistically significantly higher among dentists who preferred less stringent measures against infection transmission. Respondents who performed COVID-19 testing in their practices showed a statistically higher percentage of detected COVID-19 infections. Almost three quarters of respondents intended to adhere to strict measures against the infection transmission even after the end of the pandemic. The will to be vaccinated against COVID-19 was significantly higher than against the flu. Respondents with a positive approach to vaccination against COVID-19 were significantly more willing to be vaccinated against influenza.